Development and characterization of shape memory Cu-Zn-Al thin films - Haberkorn, N.; Lovey, F. C.; Condó, A. M.; Guimpel, J; Haberkorn, Néstor; Guimpel, Julio (Elsevier, 2010)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina